Deep-scaled fish (Osteichthyes: Actinopterygii) from the lower Permian (Cisuralian) lacustrine deposits of the Parnaíba Basin, NE Brazil. (October 2022) - Richter, Martha; Cisneros, JuanC.; Kammerer, Christian F.; Pardo, Jason; Marsicano, Claudia A.; Fröbisch, Jörg; Angielczyk, Kenneth D.
Abstract: The richly fossiliferous deposits of the Brazilian Pedra de Fogo Formation originated in an extensive aquatic system in tropical Pangaea, and grade from marginal lacustrine into marine deposits at the depocenter in the western part of the Parnaíba Basin. In addition to the well-known tetrapod and macrofloral records from these deposits, the Pedra de Fogo Formation yields extensive fish fossils indicating a diverse and abundant ichthyofauna. Among the actinopterygians, deep-bodied morphotypes are represented by whole fish as well as disarticulated dermal scales found at various localities in the states of Maranhão and Piauí. The gross morphology, ornamentation, and histology of some of these scales is highly distinctive, indicating the presence of a novel taxon ( Piratata rogersmithii gen. et sp. nov.). The external surface of a Piratata scale is covered in multiple round-to-slightly elongated tubercles. The scale lacks a ganoin cover and is made up of cellular bone and odontocomplexes of orthodentine composing the tuberculated scale surface. The scale morphology and ornamentation most closely resemble that of Cleithrolepis granulatus from the Triassic of Australia and Cleithrolepis extoni from the Triassic Stormberg Beds of South Africa, but the new taxon differs from previously described species in several diagnostic morphological features. The use of scale characters in the taxonomy of ray-finned fishes and the palaeogeographic, palaeoenvironmental, and geochronological implications of the new taxon are discussed. Highlights: A new deep-bodied fish from the Permian of Brazil is reported. Piratata rogersmithii gen. et sp. nov. is only known by isolated dermal scales. The external surface of Piratata dermal scales is covered in multiple round-to-slightly elongated tubercles. The scale lacks a ganoin cover and is made up of cellular bone and odontocomplexes of orthodentine. It is the first time this scale morphology was found in South America. The scales most closely resemble those of Cleithrolepis granulatus and Cleithrolepis extoni .